Characteristics of Single-Loop Macroreentrant Biatrial Tachycardia Diagnosed by Ultrahigh-Resolution Mapping System. (February 2018) - Kitamura, Takeshi; Martin, Ruairidh; Denis, Arnaud; Takigawa, Masateru; Duparc, Alexandre; Rollin, Anne; Frontera, Antonio; Thompson, Nathaniel; Massoullié, Gregoire; Cheniti, Ghassen; Wolf, Michael; Vlachos, Konstantinos; et al.
Abstract : Background: Biatrial tachycardia (BiAT) is a rare form of atrial macroreentrant tachycardia, in which both atria form a critical part of the circuit. We aimed to identify the characteristics and precise circuits of single-loop macroreentrant BiATs. Methods and Results: We identified 8 patients (median age, 59.5 years old) with 9 BiATs in a cohort of 336 consecutive patients from 2 institutions who had undergone AT catheter ablation using an automatic ultrahigh-resolution mapping system. Seven of the 8 patients had a history of persistent AF ablation, including septal or anterior left atrium ablation before developing BiAT. One of the 8 patients had a history of an atrial septal patch closure with a massively enlarged right atrium. Nine ATs (median cycle length, 334 ms; median 12 561 points in the left atrium; 8814 points in the right atrium) were diagnosed as single-loop macroreentrant BiATs. We observed 3 types of BiAT (1) BiAT with a perimitral and peritricuspid reentrant circuit (n=3), (2) BiAT using the right atrium septum and a perimitral circuit (n=3), and (3) BiAT using only the left atrium and right atrium septum (n=3). Catheter ablation successfully terminated 8 of the 9 BiATs. Conclusions: All patients who developed BiAT had an electric obstacle on the anteroseptal left atrium, primarily from prior ablation lesions. In this situation, mapping of both atria should be considered during AT. Because 3 types of single-loop BiAT were observed, ablation strategies should be adjusted to the type of BiAT circuit. Abstract : Supplemental Digital Content is available in the text.